Statutes of the Territory of Wisconsin: Passed by the Legislative Assembly thereof, a Session commencing in November 1838, and at an adjourned Session commencing in January, 1839, at 381 § 16 - (:unkn) unknown (My University, 1838)
"If any person shall go armed with a dirk, dagger, sword, pistol or pistols, or other offensive and dangerous weapon, without reasonable cause to fear an assault or other injury, or violence to his person, or to his family, or property, he may, on complaint of any other person having reasonable cause to fear an injury or breach of the peace, be required to find sureties for keeping the peace for a term not exceeding six months, with the right of appealing as before provided."
Keywords: SURETY